2007
DOI: 10.1016/j.otohns.2007.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 4 Registration Strategies for Computer‐Aided Maxillofacial Surgery

Abstract: Of the techniques tested for CAS registration, invasive fiducial markers are the most accurate. Skin surface landmarks, bony landmarks, and an intraoral splint are incrementally less accurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 20 publications
3
55
1
Order By: Relevance
“…In the previous studies, anatomical landmark registration was performed based on the following anatomical points: glabellum, bilateral lateral canthi, bilateramedial canthi, and nasal tip, which were difficult to select both virtually on the CBCT image and clinically during the registration procedure (Hardy et al, 2006;Metzger et al, 2007). In contrast, in our study, three anatomical points located on the occlusal level were all clearly definable, which helped improve the registration accuracy of anatomical landmarks based method.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In the previous studies, anatomical landmark registration was performed based on the following anatomical points: glabellum, bilateral lateral canthi, bilateramedial canthi, and nasal tip, which were difficult to select both virtually on the CBCT image and clinically during the registration procedure (Hardy et al, 2006;Metzger et al, 2007). In contrast, in our study, three anatomical points located on the occlusal level were all clearly definable, which helped improve the registration accuracy of anatomical landmarks based method.…”
Section: Discussionmentioning
confidence: 64%
“…In his study, the registration accuracy is below 2 mm which can not satisfy the requirements of bimaxillary surgery. Other studies demonstrate that the accuracy of anatomical landmark registration is even worse than 3 mm (Hardy et al, 2006;Metzger et al, 2007;Lubbers et al, 2011b). The main error source is that there are fewer definable bony landmarks on the cranium and lateral skull to be selected as registration point.…”
Section: Introductionmentioning
confidence: 99%
“…This device fixes the position of the patient's head in relation to the operating table (Figure 8). Infrared LEDs or reflectors are attached to the head clamp for registration, making it possible to detect all (30) found that invasive registration is more accurate than non-invasive registration.…”
Section: Registration Processmentioning
confidence: 99%
“…Previous studies have evaluated general precision (Schlaier et al, 2002;Hoffmann et al, 2005b;Metzger et al, 2007) and concentrated on navigation precision in the maxillary and periorbital region (Marmulla et al, 2004b;Marmulla et al, 2004a;Hardy et al, 2006) or precision in the cranium (Luebbers et al, 2008).…”
Section: Introductionmentioning
confidence: 99%